Chitin and Chitinases: Biomedical And Environmental Applications of Chitin and its Derivatives - Palanivel Rameshthangam; Dhanasekaran Solairaj; Gnanapragasam Arunachalam; Palaniappan Ramasamy (Journal of Enzymes, 2018)
Disposal of chitin wastes from crustacean shell can cause environmental and health hazards. Chitin is a well known abundant natural polymer extracted after deproteinization and demineralization of the shell wastes of shrimp, crab, lobster, and krill. Extraction of chitin and its derivatives from waste material is one of the alternative ways to turn the waste into useful products. Chitinases are enzymes that degrade chitin. Chitinases contribute to the generation of carbon and nitrogen in the ecosystem. Chitin and chitinolytic enzymes are gaining importance for their biotechnological applications. The presence of surface charge and multiple functional groups make chitin as a beneficial natural polymer. Due to the reactive functional groups chitin can be used for the preparation of a spectrum of chitin derivatives such as chitosan, alkyl chitin, sulfated chitin, dibutyryl chitin and carboxymethyl chitin for specific applications in different areas. The present review is aimed to summarize the efficacy of the chitinases on the chitin and its derivatives and their diverse applications in biomedical and environmental field. Further this review also discusses the synthesis of various chitin derivatives in detail and brings out the importance of chitin and its derivatives in biomedical and environmental applications.
Keywords: Chitinase